Focus on Patients' Rights: Medicī Praerogativa, or Informed Consent to Publication of Medical Pictures - Anastasiya S. Ostrovskaya ("Paediatrician" Publishers LLC, 2016)
The address to the authors focuses on the necessity of obtaining patient informed consent for publication of their personal data, and also provides a model of informed consent for publication of patients' pictures in the manuscripts submitted to academic medical journals.